Applying Routine Activities Theory to Assess On and Offline Bullying Victimization among Australian Youth. (2nd January 2023) - Malinski, Rebecca; Holt, Thomas J.; Cale, Jesse; Brewer, Russell; Goldsmith, Andrew
ABSTRACT: Juvenile populations face a substantial risk of emotional, physical, and psychological harm as a result of bullying and cyberbullying experiences. As a result, there is a need to assess the situational and individual factors contributing to the risk of bullying victimization. There is, however, little research examining cyberbullying victimization using frequency-based measures of victimization. To address this gap in the literature, this study utilized a sample of over 37, 000 youth from South Australia to explore the risk factors associated with cyberbullying victimization through a routine activities framework while controlling for verbal, social, and physical bullying. The findings noted partial support for the routine activities theory framework to account for cyberbullying victimization. Additionally, the study found differences in cyberbullying risk factors relative to the frequency with which it was reported, as well as the role of school support from peers and adults in increasing risks.